Bad Kitty Does Not Like Easter. - Bruel, Nick ([Place of publication not identified] : Roaring Brook Press, 2023)
New York Times-bestselling author/illustrator Nick Bruel's naughty feline is back in the new holiday adventure Bad Kitty Does Not Like Easter - now in a fun 9 x 9 format!
new kids book 2023 winter.
ON-ORDER RECORD
Keywords: Cats; Humorous stoires; Color; Easter; Easter egg hunts; Friendship; Picture books for children